2021
DOI: 10.1051/0004-6361/202140369
|View full text |Cite
|
Sign up to set email alerts
|

Deep transfer learning for the classification of variable sources

Abstract: Ongoing or upcoming surveys such as Gaia, ZTF, or LSST will observe the light curves of billions or more astronomical sources. This presents new challenges for identifying interesting and important types of variability. Collecting a sufficient amount of labeled data for training is difficult, especially in the early stages of a new survey. Here we develop a singleband light-curve classifier based on deep neural networks and use transfer learning to address the training data paucity problem by conveying knowled… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…However, only 23.2% RRD variables in ASAS-SN are correctly predicted. Kim et al (2021) also obtained similar results. Figure 10 in their paper showed that 91% RRD variables from ASAS-SN were classified as RRAB variables by the model which was trained based on light curves from OGLE I-band and EROS-2 B E -band.…”
Section: Classification Accuracy Comparison With Asas-sn and Oglesupporting
confidence: 63%
See 2 more Smart Citations
“…However, only 23.2% RRD variables in ASAS-SN are correctly predicted. Kim et al (2021) also obtained similar results. Figure 10 in their paper showed that 91% RRD variables from ASAS-SN were classified as RRAB variables by the model which was trained based on light curves from OGLE I-band and EROS-2 B E -band.…”
Section: Classification Accuracy Comparison With Asas-sn and Oglesupporting
confidence: 63%
“…Ongoing or upcoming surveys, such as ASAS-SN, Optical Gravitational Lensing Experiment (OGLE; Udalski 2003), Zwicky Transient Facility (ZTF; Bellm et al 2019;Masci et al 2019), China Near-Earth Object Survey Telescope (CNEOST; Wang et al 2016;Yeh et al 2020), Gaia (Gaia Collaboration et al 2016Mowlavi et al 2018), Legacy Survey of Space and Time (LSST; Ivezić et al 2019), and Wide Field Survey Telescope (WFST), will observe the light curves of billions of astronomical sources, and the large amount of data presents new challenges for the rapid identification and classification of different variability types (Kim et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through a transfer-learning method between different radio surveys, Tang et al (2019) proposed a CNN model for classifying radio galaxies. Kim et al (2021) address the problem of insufficient amount of data in variable source classification using a transfer-learning approach.…”
Section: Introductionmentioning
confidence: 99%
“…The most common usage is for classification tasks (see Cavanagh, Bekki & Groves 2021;Fremling et al 2021;Kim et al 2021 for the most recent examples), but also generative networks start to be widely adopted (see Bretonnière et al 2021;Curtis, Brainerd & Hernandez 2021;Li et al 2021, again for the latest examples). Deep Learning has also been exploited for the detection of sources, as in Sánchez-Sáez et al (2021) or Kim et al (2021) and as in our previous work (Gheller, Vazza & Bonafede 2018), where we have explored the potential of Convolutional Neural Networks (CNN) in identifying the faint radio signal from extended cosmological radio sources (such as emission from shocked gas around galaxy clusters and filaments) in noisy radio observations, which are at the limit of sensitivity of instruments like ASKAP or LOFAR. The resulting methodology, named COSMODEEP, allowed us to detect diffuse radio sources and to localize their position within large images thanks to a tiling based procedure with an accuracy of around the 90 per cent (i.e.…”
mentioning
confidence: 99%